Distinctive Mediating Effects of Subcortical Structure Changes on the Relationships Between Amyloid or Vascular Changes and Cognitive Decline - Jung, Na-Yeon; Shin, Jeong-Hyeon; Kim, Hee Jin; Jang, Hyemin; Moon, Seung Hwan; Kim, Seung Joo; Kim, Yeshin; Cho, Soo Hyun; Kim, Ko Woon; Kim, Jun Pyo; Jung, Young Hee; Kim, Sung Tae; et al. (Frontiers in Neurology, 2021)
Objective: We investigated the mediation effects of subcortical volume change in the relationship of amyloid beta (Aβ) and lacune with cognitive function in mild cognitive impairment (MCI) patients. Methods: We prospectively recruited 101 MCI patients who were followed up with neuropsychological tests, MRI, or Pittsburgh compound B (PiB) PET for 3 years. The mediation effect of subcortical structure on the association of PiB or lacunes with cognitive function were analyzed using mixed effects models. Results: Volume changes in the amygdala and hippocampus partially mediated the effect of PiB changes on memory function [direct effect = -0.168/-0.175, indirect effect = -0.081/-0.077 for amygdala/hippocampus] and completely mediated the effect of PiB changes on clinical dementia rating scale sum of box (CDR-SOB) [indirect effect = 0.082/-0.116 for amygdala/hippocampus]. Volume changes in the thalamus completely mediated the effect of lacune on memory, frontal executive functions and CDR-SOB [indirect effect = -0.037, -0.056, and 0.047, respectively]. Conclusions: Our findings provide a better understanding of the distinct role of subcortical structures in the mediation of the relationships of amyloid or vascular changes with decline in specific cognitive domains.